Desain Video Animasi 2 Dimensi Kisah Perjuangan Martha Khristina Tiahahu - Maligana, Muhammad Djafar Wittiri; Rochmawati, Irma (Fakultas Desain Universitas Komputer Indonesia, 2022)
Hero is a term for anyone who is extraordinarily meritorious to his nation. Through the figure of a hero, a symbol of struggle, defending the truth, and sacrifice, always maintained and passed down from generation to generation. The hero is also one of the important figures that must be known by all the people around him, not only remembering in his heart and thanking him, but also by imitating the attitudes and actions of the heroes. However, heroes who have many values that can be imitated are increasingly being forgotten by the younger generation. Early recognition is needed so that children can recognize and know the heroes of national independence in order to become a better generation, especially teenagers in Indonesia. The purpose of the design is to introduce the history and national independence hero figures from the Maluku Islands, namely Martha Khristina Tiahahu. The media used as a solution to the problem is by using interactive information communication, looks fun, and interesting, also is in demand by the public, especially teenagers, and can be accessed easily so that information about this problem can be spread out to the general public, especially students. Animation is a film that is the result of hand work in the form of moving images.